Understory plant dynamics following a wildfire in southern Patagonia - Ruggirello, Matthew Joseph; Soler Esteban, Rosina Matilde; Bustamante, Gimena Noemi; Lencinas, María Vanessa (Forest Ecology and Management)
Historically, wildfires have occurred infrequently in the Subantarctic forests on the island of Tierra del Fuego in southern Argentina: wildfires on the landscape are sporadic and exclusively human-caused. As a result of this, post-fire effects on native vegetation are largely unknown. In November of 2008, a wildfire started near a sawmill in the central part of the island. Six pre-established research plots located in Nothofagus antarctica (ñire) dominated forests burned, impacting a long-term study of understory vegetation dynamics. In 2008 (pre-fire), two 10 m long permanent transects were established per plot (n = 12), where we evaluated species richness and plant cover using a point intersection method at 20 cm intervals, resulting in 50 points per transect. After the fire, we continued sampling to evaluate post-fire understory response in burned and unburned plots. The first post-fire sampling occurred in January 2009, and was repeated semi-annually in burned and unburned plots (2010–2014, 2016, 2018, 2020, and 2021). Data were analyzed using GLMMs (Generalized Linear Mixed Models) and multivariate analyses (Nonmetric Multidimensional Scaling, Multi-Response Permutation Procedures). Total species richness and cover decreased the year following the fire, but recovered by 2010, eventually surpassing pre-fire levels. Increases in species diversity were due principally to an increase in exotic species richness (F = 4.73; p < 0.001) and cover (F = 51.59; p < 0.001). For native species, richness followed the same trend as total vegetation, but cover decreased drastically following the fire (F = 19.77; p < 0.001) and had not recovered to pre-fire levels by 2021. MRPP revealed that plant assemblage in burned plots differed from those in unburned plots the season following the fire (p < 0.001) and still differed 7–12 years post-fire (p < 0.001). Wildfire in Tierra del Fuego produces changes in understory dynamics that create non-forest plant assemblages dominated by exotic species; these changes last ...